PENGEMBANGAN MEDIA SPINNING WHEEL GAME PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI SEKOLAH - Setiawan, Ridwan; Ramadila Aulia, Sri (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2024)
Elementary school age is vulnerable to disease attacks caused by a lack of hygiene and health. PHBS indicators set by the Ministry of Health can protect school children from common health problems, one of which is diarrhea (Kusumawardani et al., 2019). The incidence of diarrhea in Bandung Regency is the third highest at 101,890 cases out of 27 regions in West Java Province (West Java DHO, 2021). This study aims to develop media Spinning wheel game Clean and Healthy Living Behavior (PHBS) at School for SDIT Al-Huda Cipetir students with the ADDIE development research model. This research uses development research with the ADDIE approach (Analyze, Design, Develop, Implement, Evaluate). The sample amounted to 32 students of SDIT Al-Huda Cipetir Bandung Regency, sampling using the Total Sampling Technique, Media Spinning wheel game has a diameter of 50 cm made of MDF wood, equipped with information cards made of 260 gsm artpaper measuring 10.5 x 14.5 cm. Obtaining a value of 75% with a decent category from material experts, 100% with a very feasible category from media experts and 74.31% with a decent category from small-scale trials. There is an effect of using spinning wheel game media regarding PHBS in Schools with an increase of 28.75%. The media is declared feasible by experts and there is an effect of providing Spinning wheel game media on PHBS in schools.